Core-size dispersity dominates the self-assembly of polymer grafted nanoparticles in solution - Bachhar, Nirmalya; Kurnaraswamy, Guruswamy; Kumar, Sanat K. (Macromolecules, 2019)
In polymer-grafted nanoparticles (PGN), covalent tethering of apolar polymer chains to a polar inorganic nanoparticle core induces the formation of self-assembled aggregates. Since the nature of these aggregates determines bulk mechanical and transport properties, it is of importance to understand the factors that determine the underlying assembly processes. In the literature, the solution assembly of PGNs has been understood in analogy to small-molecule amphiphiles. However, in any experimental realization, PGNs are invariably characterized by additional structural complexity, such as the distributions in the inorganic core size and in the grafted chains (both in their length and grafting density). These strongly influence the assembly of amphiphilic PGNs. We have previously demonstrated that dispersity in core size qualitatively affects the structure of PGN aggregates, and Jayaraman et al. demonstrated the effect of grafted chain-length dispersity. The combined effects of dispersity in the size of the core and grafted chains have not been explored previously. Here, we develop a model that builds on the work of Daoud and Cotton to explore a wide parameter space of PGN with dispersity simultaneously in core size and grafted chain length. We demonstrate that dispersity in core size is the dominant factor affecting the self-assembled solution structure of PGN aggregates. Our work suggests the importance of focusing on synthetic strategies for control of core-size dispersity to control aggregate structure in PGN.

Critical role of processing on the mechanical properties of cross-linked highly loaded nanocomposites - Suresh, Karthika; Chowdhury, Arindam; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Polymer nanocomposites are frequently not at equilibrium-therefore, the structure and properties critically depend on the protocol followed in their preparation. Here, we demonstrate that the elastic-brittle transition in highly loaded ice-templated polymer nanocomposites is sensitively determined by the conformation of polymer chains during nanocomposite preparation. Macroporous polymer nanocomposites are synthesized using two preparation pathways, both exhibiting minor modifications of the ice-templating method wherein an aqueous dispersion of nanoparticles, polymers, and cross-linkers is frozen. In one method, the matrix polymer is cross-linked in the presence of ice, whereas in the other method, the ice is removed by freeze-drying before the polymer is cross-linked. Although all measurable structural metrics are practically identical for the two composites, they exhibit qualitatively different mechanical properties. Nanocomposites cross-linked in the presence of ice show exceptional resilience, recovering elastically from large compression for very high nanoparticle loadings-in some instances, above 90% by weight. Here, the critical particle loading for the elastic- brittle transition is dependent on the molecular weight of the polymer. In comparison, samples cross-linked after freeze-drying appear structurally identical but turn brittle at much lower particle loadings (about 60% by weight), independent of the matrix polymer molecular weight. We rationalize these differences in terms of the conformational state of the polymer during cross- linking. In the former case, polymer chains are in good solvent during nanocomposite preparation, while after lyophilization, they are in a poor solvent. The large spatial extent of well-solvated chains and chain-chain overlap during cross-linking results in the formation of intermolecular cross-links, and we obtain elastic nanocomposites even at high nanoparticle loadings. In contrast, for chains in collapsed conformations in a bad solvent, chain connectivity during cross-linking is achieved only for much lower particle loadings. Our results reiterate that the sensitivity of polymer conformations to different processing methods can result in large differences in properties, even though their consequences on structural characteristics are effectively indistinguishable.

Colloidal assembly by directional ice templating - Biswas, Bipul; Misra, Mayank; Bisht, Anil Singh; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Soft Matter, 2021)
We investigate directional ice templating of dilute aqueous colloidal particle dispersions and examine the nature of the assemblies that result. We coat micron-size polystyrene colloids with cross-linkable polymer (polyethyleneimine, PEI), add cross-linker, and subject this dispersion to unidirectional freezing. We work at sufficiently low colloid concentrations, such that the particles do not percolate on freezing. When the aqueous dispersion freezes, ice crystals force polymer-coated particles and cross-linker into close proximity. This results in the formation of cross-linked clusters of particles at ice crystal boundaries. We vary the particle volume fraction from phi similar to 2.5 x 10(-3) to phi similar to 5.0 x 10(-2) and observe that there is a transition from isolated single particles to increasingly large sized clusters. Most of the clusters formed under these conditions are either linear, two-particle wide chains, or sheet-like aggregates. The probability (P-n) of clusters containing n particles (n > 2) obeys a power law P-n similar to n(-eta), where eta strongly depends on the particle concentration in the dispersion, varying from 2.10 (for phi similar to 5.0 x 10(-2)) to 3.03 (for phi similar to 2.5 x 10(-3)). This change in eta is qualitatively different from the case of isotropic freezing, where eta is particle concentration-independent and depends only on the ice nucleation density. To understand the differences between isotropic and directional ice templating, we performed lattice simulations of a highly simplified model, where ice crystals grow at a constant rate to force clustering. We ignore hydrodynamic interactions and ice growth instabilities. Despite ignoring these experimental details, the simulations capture the experimental results, nearly quantitatively. As the ice crystals grow and the space available to the colloids ``closes up'' so that the particles cluster to form aggregates, crystallization protocol-induced differences in the geometry of these ``closed up'' spaces determine the scaling behaviour of P-n.